Tracking red blood cells in microchannels: a comparative study between an automatic and a manual method - Pinho, Diana (2014)
Image analysis is extremely important to obtain crucial information about the blood phenomena in microcirculation. The current study proposes an automatic method for segmentation and tracking red blood cells (RBCs) flowing through a 100 μm Glass capillary. The original images were obtained by means of a confocal system and then processed in Matlab using the Image Processing Toolbox. The automatic measurements obtained with the proposed automatic method are compared with a manual tracking method using a plugin from ImageJ.